2019
DOI: 10.1002/cncr.32458
|View full text |Cite
|
Sign up to set email alerts
|

Chinese nonmedicinal herbal diet and risk of nasopharyngeal carcinoma: A population‐based case‐control study

Abstract: Background An association between a nonmedicinal herbal diet and nasopharyngeal carcinoma (NPC) has often been hypothesized but never thoroughly investigated. Methods This study enrolled a total of 2469 patients with incident NPC and 2559 population controls from parts of Guangdong and Guangxi Provinces in southern China between 2010 and 2014. Questionnaire information was collected on the intake of traditional herbal tea and herbal soup as well as the specific herbal plants used in soups and other potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
(97 reference statements)
2
10
1
Order By: Relevance
“…However, this current metaanalysis is limited by disparity in the parameters studied by our data source. This investigation found a contrary association between NPC risk and tea consumption from a previous report by Lin et al (2019), which revealed that the risk of NPC was increased among people who consume herbal tea for up to five years compared to those who cosumed less. Therefore, few studies have reported that, inconsistent habit of tea drinking could lead to NPC risk.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this current metaanalysis is limited by disparity in the parameters studied by our data source. This investigation found a contrary association between NPC risk and tea consumption from a previous report by Lin et al (2019), which revealed that the risk of NPC was increased among people who consume herbal tea for up to five years compared to those who cosumed less. Therefore, few studies have reported that, inconsistent habit of tea drinking could lead to NPC risk.…”
Section: Discussioncontrasting
confidence: 99%
“…Use of Asian traditional herbal medicines was associated with a 2-to 4-fold excess risk of NPC in some case-control studies (61,65,70,102), but not others (72)(73)(74)88). Two studies, including ours, found inverse associations of NPC risk with consumption of Cantonese-style slowcooked herbal soup (83,103), including nine specific plant species commonly used in such soups (103); however, these studies found conflicting inverse and null results, respectively, for consumption of Cantonese-style herbal teas. Associations with use of traditional herbal medicines are susceptible to confounding by indication and, in casecontrol studies, reverse causation.…”
Section: Traditional Herbal Medicinesmentioning
confidence: 59%
“…However, through our previous case-control study in Sihui, we found that plants frequently used in herbal soups include Semen coicis , Bulbus lilii , Polygonatum odoratum , Fructus lycii , etc, and the most prevalent herbs used in teas are Chrysanthemum morifolium , Prunella asiatica , Flos lonicerae , Glycyrrhiza uralensis , Helicteres angustifolia , etc. ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Distinguished with herbal tea for the main purpose of being anti-inflammatory, people consume herbal soup with discrepant herbal ingredients to maintain energy and improve immunity. According to our previous study, nine commonly used herbal plants species (Ziziphus jujuba, F. lycii, Codonopsis pilosula, Astragalus membranaceus, S. coicis, Smilax glabra, Pristimantis calcaratus, Morinda officinalis, and Atractylodes macrocephala) in herbal soups might have been involved in the anticancer effect through inducing apoptosis, inhibiting cancer cell migration and differentiation, or regulating signaling pathway (19,(38)(39)(40)(41)(42). As many studies in vitro have shown that bioactive components in herbal soup may inhibit EBV (25,43,44), the most important risk factor for NPC (2), an association between herbal diet and NPC through antiviral biological mechanisms have often been hypothesized but never thoroughly investigated.…”
Section: Comparison With Other Studies and Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation